Advances in 3D printing for the repair of tympanic membrane perforation: a comprehensive review - Xue, Hao; Chen, Shengjia; Hu, Yi; Huang, Juntao; Shen, Yi (Frontiers in Bioengineering and Biotechnology, 2024)
Tympanic membrane perforation (TMP) is one of the most common conditions in otolaryngology worldwide, and hearing damage caused by inadequate or prolonged healing can be distressing for patients. This article examines the rationale for utilizing three-dimensional (3D) printing to produce scaffolds for repairing, compares the advantages and disadvantages of 3D printed and bioprinted grafts with traditional autologous materials and other tissue engineering materials in TMP repair, and highlights the practical and clinical significance of 3D printing in TMP repair while discussing the current progress and promising future of 3D printing and bioprinting. There is a limited number of reviews specifically dedicated to 3D printing for TMP repair. The majority reviews offer a general overview of the applications of 3D printing in the broader realm of tissue regeneration, with some mention of TMP repair. Alternatively, they explore the biopolymers, cells, and drug molecules utilized for TMP repair. However, more indepth analysis is needed on the strategies for selecting bio-inks that integrate biopolymers, cells, and drug molecules for tympanic membrane repair.